PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SEDERHANA SISWA KELAS III SD NEGERI 001 TELUK BERINGIN - Desvilia, Riska Desvilia; Kurniaman, Otang Kurniaman; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this research is the low student essay writing skills, as seen from the average value of students is 70,4. Of the 32 students who achieve grades above KKM only 12 students (37,5%), while students who heve not reached the KKM many as 20 students (62,5%), the value specified KKM is 75. Based on these problem s need classroom action research conducted by applying the model of contextual teaching and learning. This study aims to improve the writing skills of a simple essay third grade students of SDN 001 Teluk Beringin of school year 2014/2015 the number of students as many as 32 people consisting of 19 male students and 13 female students. This research was conducted by three cycles. At each cycle I,II, and III consist of two face to face meetings and one daily test at the end of the cycle. With the applied model of contextual teaching and learning can improve essay writing skills, it can be seen fron the increase of students writing skills base score is the average of 70,4 increased by 2,9 % to 72,5 in the first cycle, and the cycle II increased by 7,9% to 76, and the third cycle increased by 17,7% to 82,9. The percentage of teachers activity also increased, as seen from the percentage of teachers in the first cycle of activity first meeting 62,5% increase at meeting the second becomes 68,75%, on the second cycle increased in the first meeting , namely 75 % and increased in the second meeting to 81,25%, and rose again on the third cycle of the first meeting be 87,5%, and increased in the second meeting to 93,75%. The percentage of student activity also increased in the first cycle the first meeting 62,5% increase to 68,75% in the second meeting, on the second cycle increased in the first meeting 75%, and increased in the second meeting of 81,25%, in the third cycle increased in the first meeting of 87,5%, and increased in the second meeting becomes 93,75%. Based on the research results can be concluded that aplication of contextual teaching and learning models enhance the writing skills of third grade student of SDN 001 Teluk Beringin. Key word: model of contextual teaching and learning, writing skills